AVOCADO BASED FOOD PRODUCT DIVERSIFICATION: HIGH-FIBER STEAMED CAKE AT SCHOOL OF THEOLOGY CIANJUR - Dr. Adolf J.N. Parhusip; Nuri Arum Anugrahati; Ratna Handayani; Intan Matita; William Christian; Michelle Caroline Setiawan (Universitas Pelita Harapan, 2026)
This Community Service activity aims to improve community skills in diversifying local food products based on avocado through a training session on making high fiber steamed cakes. The activity was conducted on April 24–25, 2025, at the STT-SAPPI Campus, Palalangon Village, Ciranjang District, Cianjur Regency, involving 44 participants consisting of pastoral candidates. The implementation method included lectures, demonstrations of avocado steamed cake preparation, distribution of recipe brochures, and interactive question-and-answer sessions. This activity was designed in alignment with STT-SAPPI's holistic curriculum, which focuses on rural ministry, providing practical knowledge for future ministers to help develop local economies through food processing. Evaluation results showed that 100% of participants considered the activity beneficial and were willing to join similar future events, while 88% expressed high satisfaction with its implementation. This activity proves that simple food processing training can serve as a tool for community empowerment and increasing the value of local agricultural products. It also demonstrates that applicable food technology skills can serve as a strategic asset for pastoral candidates in fostering economic self-sufficiency among church communities in their areas of ministry.